Asymmetries of the central sulcus in young adults: Effects of gender, age and sulcal pattern. Issue 44 (August 2015) - Sun, Bo; Ge, Haitao; Tang, Yuchun; Hou, Zhongyu; Xu, Junhai; Lin, Xiangtao; Liu, Shuwei
Highlights: The gender and age-related asymmetries of the central sulcus in early adulthood using a parametric ribbon method. The 3D anatomic morphology of the CS were presented using 5 sulcal parameters, including sulcal depth position-based profile, average depth, average width, top length and bottom length. The lateralization performances of the central sulcus are sexually different. Males may undergo a faster progress of aging compared to females. Abstract: In this study, we clarified the gender and age-related asymmetries of the central sulcus (CS) in early adulthood using a parametric ribbon method. The CS was reconstructed and parameterized automatically from 3D MR images of 112 healthy right-handed subjects. The 3D anatomic morphology of the CS was presented using 5 sulcal parameters, including sulcal depth position-based profile (DPP), average depth (AD), average width (AW), top length (TL) and bottom length (BL). Asymmetry differences in DPPs were found in the medial and lateral part of the CS. In addition, significant gender differences were observed in the medial and middle parts of the right CS DPPs but scattered in the left side. We found leftward asymmetries of TL in males, but rightward asymmetries of AW in females. Males had a greater AW than females in the right hemisphere. Moreover, the females had bilateral longer TL and a longer left BL than did males. We also found significant age-related reductions in bilateral TL and increases in bilateral AW, with males presenting more obvious age-related change than females. There were sexual differences of the CS patterns, in which Type b was the most dominant sulcal pattern in males, whereas Type a was dominant in females. Three-way ANOVA revealed sexual and asymmetry changes of TL and BL among different CS patterns. Our findings indicate that the lateralization performances of the CS manifest as sexually and regionally different. In addition, it is suggested that males may undergo a faster progress of aging compared to females.